85.1k views
1 vote
Expand & simplify 5 ( y + 2 ) − 2 ( y − 5 )

User David Rees
by
6.3k points

2 Answers

12 votes


\textsf {Applying the distributive property :}


\implies \mathsf{5(y + 2) - 2(y - 5)}


\implies \mathsf {5(y) + 5(2) - 2(y) - 2(-5)}


\implies \mathsf {5y + 10 - 2y + 10}


\textsf {Combining like terms :}


\implies \textsf {5y - 2y + 10 + 10}


\implies \textsf {3y + 20} (Final answer)

User WebSmithery
by
5.9k points
1 vote

Answer:


  • \sf 3y+20

Explanation:


\sf 5 ( y + 2 ) - 2 ( y - 5 )

Expand

Use the distributive property to multiply 5 by y+2, and -2 by y-5.


\sf 5y+10-2y+10

Combine like terms.


\sf 3y+10+10


\sf 3y+20

_________________

User Igor Borisenko
by
6.1k points